2023
DOI: 10.2196/44216
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a Digital Mental Health Program for Patients With Sickle Cell Disease: Qualitative Study

Abstract: Background Depression and other mental health disorders are prevalent among people living with chronic health conditions. Although digital cognitive behavioral therapy (CBT) is considered an effective treatment, African American individuals are less likely to engage in and adhere to digital therapies for mental health disorders compared with White individuals. Objective The aim of this study was to understand digital CBT mental health treatment percepti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Prior to adapting the app, guided focus groups were conducted to determine ways to enhance the app to increase engagement for minorities living with SCD ( 38 ). Based on the findings of this study, and guided by the FRAME, a framework for adapting interventions ( 39 ) we identified areas of adaptation related to the content, contextual factors, and the training/education of staff delivering the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to adapting the app, guided focus groups were conducted to determine ways to enhance the app to increase engagement for minorities living with SCD ( 38 ). Based on the findings of this study, and guided by the FRAME, a framework for adapting interventions ( 39 ) we identified areas of adaptation related to the content, contextual factors, and the training/education of staff delivering the intervention.…”
Section: Methodsmentioning
confidence: 99%